PARADIGMA BARU MENGEMAS DAKWAH MELALUI MEDIA TELEVISI DI ERA GLOBALISASI - Fatmawati Fatmawati (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
In this global era, da’wah through television has an important role in human development, especially akhlaq,moral, and character development. At present, television should deliver da’wah programs with a new paradigm adopting 5basic elements: 1) as the centre of information for all social classes; 2) as a media of education and instruction, whichparticipate in socializing religious values so that it can promote the birth of intellectual and religious Muslim society (khoiruummah); 3) da’wah package with direct or indirect interactive methods with da’i or da’iyah can give a fast and appropriatesolution to the society; 4) the existence of actual and creative da’wah programs on TV can balance the uneducativeprograms, especially foreign cultures which come into society without any boundaries; 5) television can be a means ofeconomic and social development among Muslims through producing marketable da’wah programs, such as talk show,religious drama program (sinetron), Islamic movies, etc. and this can be the source of financial funding for Islamic preaching.